2013
DOI: 10.1103/physreva.87.023605
|View full text |Cite
|
Sign up to set email alerts
|

Two-component few-fermion mixtures in a one-dimensional trap: Numerical versus analytical approach

Abstract: We explore a few-fermion mixture consisting of two components which are repulsively interacting and confined in a one-dimensional harmonic trap. Different scenarios of population imbalance ranging from the completely imbalanced case where the physics of a single impurity in the Fermisea is discussed to the partially imbalanced and equal population configurations are investigated. For the numerical calculations the multi-configurational time-dependent Hartree (MCTDH) method is employed, extending its applicatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 55 publications
3
47
0
Order By: Relevance
“…One-dimensional (1D) systems are among the most widely studied problems in physics, especially due to their invaluable pedagogical properties and their more friendly manipulation of mathematical expressions both analytically and numerically, which often guide us through the understanding of interesting physical systems [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22]. Furthermore, 1D structures such as nanotubes and nanowires, among others, may be highly relevant in technological applications [23].…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional (1D) systems are among the most widely studied problems in physics, especially due to their invaluable pedagogical properties and their more friendly manipulation of mathematical expressions both analytically and numerically, which often guide us through the understanding of interesting physical systems [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22]. Furthermore, 1D structures such as nanotubes and nanowires, among others, may be highly relevant in technological applications [23].…”
Section: Introductionmentioning
confidence: 99%
“…These authors investigated the dimensional crossover from a three-dimensional to a quasi one-dimensional trap but reported partial data for stricly one-dimensional fermions and no data for bosons. Other approaches for three particles in a trap in one dimension include group-theoretical [67] and geometrical analyses [68], multiconfigurational time-dependent Hartree method [63,[69][70][71], ansatz correlated wave functions [63,71], effective-interaction approaches [29,70], density functional theory [72], as well as exact results in the limit of infinite repulsion [34,73,74].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental progress has generated great interest for few-body problems in one-dimensional geometries for both bosonic [21][22][23][24][25][26][27][28], fermionic [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], and mixed systems [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Recently, it has been shown that for strong short-range repulsive interactions a 1D two-component Fermi system in a harmonic trap exhibits strong magnetic correlations already at the three-body level [37,40].…”
Section: Introductionmentioning
confidence: 99%